Study of Platelets Derangement in Toxemia of Pregnancy - Sah, Archana Kumari; Rana, Sarita; Pal, Manindra Nath (Journal of College of Medical Sciences-Nepal, 2020)
Background: Toxemia of pregnancy has been identified as multisystem disorder associated with high maternal and neonatal complications. Platelets, Liver enzymes and Lactic Acid Dehydronagenase (LDH) derangements have been shown to be associated with the severity of the disorder. The present study aims to find the association of toxemia of pregnancy with the derangement of platelets count at our centre. Methods: The study was a prospective study conducted with sixty cases of toxemia of pregnancy during the study period of one and half years (December 2014 to July 2016). The statistical evaluation was calculated using SPSS software version 20.1 with student t-test and Anova. Results: The incidence of toxemia of pregnancy was found to be 10.45%. The majority of cases (66.70%) were between 20 to 29 years of age. Most of the cases 68.34% were primigravida. Mild pre-eclampsia was seen in 45% of cases and severe pre-eclampsia in 38.30% of cases. Eclampsia was seen in 10% of cases and 6.7% of the cases of chronic hypertension developed superimposed preeclampsia. Mean platelets count observed in severe pre-eclampsia toxemia (PET) was 1. 21 lac/mm3 in eclampsia was 1.03 lac/mm3 (P-Value 0.001). The mean platelets count was statistically significant and correlated with the severity of the diseases. Conclusions: The study concluded with the observation that derangements of platelets counts significantly correlate with the severity of the diseases and its early detection during pregnancy can reduce eventual maternal and fetal complications. Keywords: eclampsia; hypertensive disorder of pregnancy; platelets count; pre-eclampsia; toxemia of pregnancy.